(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
The article provides an in-depth teaching of the theoretical foundations of art in music education and thereby an explanation of the social significance of art and the processes associated with it, the effectiveness of artistic and aesthetic influence, its social significance.